2017
DOI: 10.3945/ajcn.116.137158
|View full text |Cite
|
Sign up to set email alerts
|

Choline and its metabolites are differently associated with cardiometabolic risk factors, history of cardiovascular disease, and MRI-documented cerebrovascular disease in older adults,

Abstract: Background: There is a potential role of choline in cardiovascular and cerebrovascular disease through its involvement in lipid and one-carbon metabolism. Objective: We evaluated the associations of plasma choline and choline-related compounds with cardiometabolic risk factors, history of cardiovascular disease, and cerebrovascular pathology. Design: A cross-sectional subset of the Nutrition, Aging, and Memory in Elders cohort who had undergone MRI of the brain (n = 296; mean 6 SD age: 73 6 8.1 y) was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 43 publications
3
40
0
1
Order By: Relevance
“…In the same study, higher plasma phosphatidylcholine was associated with characteristics of both favorable (higher high‐density lipoprotein cholesterol and lower body mass index) and unfavorable (higher low‐density lipoprotein cholesterol and triglycerides) cardiometabolic risk. These findings suggest divergent roles of choline metabolites in the pathogenesis of cardiometabolic risk factors and cerebrovascular disease . Similarly, in our study, we have observed that baseline choline concentrations are marginally associated with the prevalence of being overweight and obesity (odds ratios [95% CIs] per 1‐SD increase, 1.13 [1.00–1.29] and 1.15 [1.00–1.34], respectively).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the same study, higher plasma phosphatidylcholine was associated with characteristics of both favorable (higher high‐density lipoprotein cholesterol and lower body mass index) and unfavorable (higher low‐density lipoprotein cholesterol and triglycerides) cardiometabolic risk. These findings suggest divergent roles of choline metabolites in the pathogenesis of cardiometabolic risk factors and cerebrovascular disease . Similarly, in our study, we have observed that baseline choline concentrations are marginally associated with the prevalence of being overweight and obesity (odds ratios [95% CIs] per 1‐SD increase, 1.13 [1.00–1.29] and 1.15 [1.00–1.34], respectively).…”
Section: Discussionsupporting
confidence: 81%
“…These findings suggest divergent roles of choline metabolites in the pathogenesis of cardiometabolic risk factors and cerebrovascular disease. 31 Altogether, these findings suggested a relationship between these metabolites and cardiovascular risk factors. The associations between dietary choline and betaine on the risk of CVD have been evaluated in several prospective studies.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…SN-glycero-3-9 Journal of Pregnancy phosphocholine is a phospholipid that serves a precursor to choline biosynthesis and an intermediate in the metabolism of phosphatidylcholine. Choline metabolites have been associated with unfavorable cardiometabolic risk factors, while phosphatidylcholine has been associated with a lower odds of hypertension [64]. L-Kynurenine is a metabolite derived from the amino acid L-tryptophan and used in the production of niacin.…”
Section: Discussionmentioning
confidence: 99%
“…As one grows older, the risk suffering from diabetes, 14 hypertension, 15 cardiovascular, and cerebrovascular diseases increased. 16 These diseases are also significant risks of cardiac arrest. 17 Cardiac etiology was the most common reason for cardiac arrest, about 50% to 60% of which is induced by heart-related diseases, such as myocardial infarction, arrhythmia, or cardiac failure, and so forth.…”
Section: Verification Of Prediction Modelmentioning
confidence: 99%